Laboratory Calibration of TDR Probes for Simultaneous of Measurements Soil Water Content and Electrical Conductivity. Issue 13 (20th July 2019) - Agah, A. Erfani; Meire, P.; De Deckere, E.
ABSTRACT: Accurate measurement of water content ( θ ), apparent electrical conductivity (ECa ) of soils, and soil solution electrical conductivity (ECw ) is critical for a better management of irrigation water and the effective monitoring and control of soil salinity. In this paper, we demonstrate the design and validation of an identical time domain reflectometry (TDRWO) probe for accurate and non-destructive measurements of ECw. Two calibration functions were used to determine the soil-water content by TDR. Theses relations were verified by laboratory experiment over a wide range of θ and bulk density (BD) for dune sand. The exact length and the impedance of all TDR-probes were calibrated using the WinTDR procedure. Estimates of ECw were based on θ and the bulk ECa using a special modeling approach which applies long-time TDR waveform analysis. The geometrical disposition of the matrix phase factors ( τ and β) was calculated by immersing the TDR probe in sodium chloride (NaCl) solutions of different electrical conductivities in pressure cells wetted and drained with each of these NaCl solutions. The reliability of the TDRWO was validated/proven under laboratory conditions. The laboratory experiment consisted in inserting the TDR probe into a pressure cell packed with mixed sand and 2-mm sieved loam soil that was subsequently wetted and drained with different NaCl solutions at various pressure heads. The ECw estimated by TDRWO was compared to the ECw measured in the draining solutions after they stabilized in the soil porous system. The τ and β factors calculated for the ceramic disks sets were 1.991 and 4.312, respectively. In the laboratory experiments, high and therefore significant correlations (R 2 = 0.986; P < .001) were found between the ECw estimated by the TDRWO and the corresponding ECw values measured in the column-drainage. These results demonstrate that the TDRWO is an instrument which allows researchers to accurately estimate soil solution salinity independently of the soil water content and the porous medium in which the TDR probe is installed. Test results showed that the TDR method has high accuracy for monitoring soil water content but is less accurate in monitoring soil electrical conductivity across a water content range of about ≤0.03cm 3 /cm 3 . Regression analysis between TDR-Volumetric water content (ϴv ) and weighing method – ϴv showed good correlation with an R 2 of 0.97 and 0.98 during two laboratory experiments.